ROLE OF EVALUATION OF WRIST SOFT TISSUE BY ULTRASOUND IN PREDICTION OF ACTIVATION AND REMISSION IN PATIENTS WITH RHEUMATOID ARTHRITIS - Funda Demir; Haydar Gök; Gülay Dinçer; Polat Koşucu; Mustafa Salih (Archives of Rheumatology, 2002)
This study examined the validity of soft tissue ultrasound and power doppler ultrasound in the assessment of disease activity in RA. Fifty patients with diagnosis of RA according to ACR criteria were enrolled (38 females, 12 males) in the study. Symptoms, joint swelling and pain, patient’s self-assessment of disease activity, physician’s global assessment, and Stanford Health Assessment score (HAQ) were recorded by an interview. Laboratory investigations included blood count, sedimentation rate, CRP, RF. Ultrasonographic examination of extensor tendons of bilateral wrists was performed. Sensitivity and specificity for RA disease activity were %52.6 and %100 for USG, %73.6 and %100 for PDU. Probability of remission increased almost 17 times (%95 CI: 1.44-200.4) when both tests were normal compared to at least one positive test. Study findings provided evidence for the criterion validity of USG and PDU in the assessment of disease activity in RA. As a conclusion, we suggest the use of tendon USG which has a higher sensitivity as an initial test (screen test) then PDU which has a higher specificity as a second test (diagnostic).